Developments in Nanosuspension Technology for Enhancing the Solubility and Bioavailability of Poorly Soluble Drugs - Saravanakumar Kasimedu; Srividya Kanchibhotla; Anusha Neelampalle; Sai Mahesh Chengalasetty; Lithin Sadum; Chanhukya Dharmavaram; Nagaveni Pommala; Mallikarjuna Gandla (Pharmaceutical Science: New Insights and Developments Vol. 3, 2025)
Drug formulation is greatly impacted by solubility around 40% of recently generated medications have poor water solubility. Improved solubility is a crucial step in the formulation of drugs and nanosuspensions have shown promise in tackling this problem. Nanosuspensions are made using a variety of methods including solvent evaporation, high-pressure homogenization and media milling. In addition to increasing a drug’s solubility and bioavailability, nanosuspensions may affect its pharmacokinetics which may improve its safety and therapeutic effectiveness. The main objectives of recent studies and developments in nanosuspension technology have been to enhance formulation techniques, boost in-vitro and in-vivo performance and broaden their use in a variety of therapeutic domains. Additionally, the manufacturing and characterization of nanosuspensions have been improved by the use of patented techniques. In the formulation of nanosuspensions, key parameters like particle size, surface area, entrapment efficiency, and drug loading play a significant role in determining the overall performance of the drug. These factors directly influence the bioavailability, stability, and therapeutic effectiveness of the formulation. Balancing these parameters is critical to achieving the desired outcomes in drug delivery. This review emphasizes the promise of nanosuspensions as a flexible remedy for medications that are poorly soluble, highlighting their importance in contemporary drug research and their noteworthy influence on pharmaceutical innovation.